The Implementation of Integrated Character Education Outcomes in Elementary Schools - Surmana, Surmana; Lestari, Neta Dian; Valianti, Reva Maria; Sasongko, Rambat Nur; Kristiawan, Muhammad; Danim, Sudarwan (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study evaluated the implementation of integrated character education in elementary schools in the city of Palembang and measure the achievement of the results. The implementation of integrated character education in several cities in Indonesia has not shown encouraging results. This study is a survey method, conducted at 20 elementary schools in Palembang with descriptive statistics, frequency distribution, and histogram. Data collection techniques were obtained through in-depth interviews, observation, documentation, checklists, and questionnaires. The results showed that the implementation of integrated character education in elementary schools has not been encouraging. Empirical evaluative findings show that in the fifth grade the highest percentage is 36.33% and in the sixth grade, 30.33% of the 600 elementary school students in the city of Palembang studied still in the Good enough category. The presence and role of classroom teachers who are specifically entrusted with the role of the transmitter of character education or heart education are sometimes overwhelmed and the role of guidance and counseling teachers at the elementary school level is not very visible or even not involved at all, as seen in most elementary schools in Indonesia. This paper recommend to provide hours of classical tutoring services.